Edukasi Kesehatan Reproduksi bagi Remaja di Sekolah Minggu GKKD Buper Waena Distrik Heram Kota Jayapura - Ferry Rhendra Pananda Putra Sitorus; Irene Daniella Merahabia (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
The increasing spread of HIV/AIDS in Jayapura City requires immediate and sustainable preventive efforts, particularly through reproductive health education for adolescents. This program aimed to improve adolescents’ understanding of reproductive health, puberty changes, and behaviors that may increase the risk of HIV/AIDS transmission. The activity was conducted for adolescents participating in Sunday School at GKKD Buper Waena, aged between 10 and 15 years. The program was carried out in April 2025 through counseling sessions, question-and-answer activities, and focus group discussions. These approaches were chosen to provide participants with an interactive learning experience while also creating opportunities for them to share their personal experiences and perspectives related to reproductive health. A total of fifty adolescents participated enthusiastically in the activity. During the sessions, participants asked various questions that were answered directly by the speakers to clarify their understanding of reproductive health and risky behaviors. In addition, six focus group discussions were conducted to discuss participants’ personal experiences regarding puberty, friendships, dating, and behaviors such as kissing. The results of the activity indicate that reproductive health education can improve adolescents’ knowledge, awareness, and skills in maintaining personal health and avoiding behaviors that may increase the risk of HIV/AIDS transmission.